Modeling of deformation of a plate using piezoelectric elements located on its surface - Iurlova, Nataliya Alekseyevna; Oshmarin, Dmitriy Aleksandrovich; Sevodina, Natal’ya Vital’yevna; Kovalev, Igor’ Evgen’yevich (Computational Continuum Mechanics, 2019)
One of the directions of using piezoelectric elements in modern technology is related to their use for controlling the shape of a structure under the influence of operational loads. A problem of change in the shape (geometry) of the structure can be caused, for example, by the need for minimization of displacements in certain regions which are induced by the impact of different types of loads, or vice versa, for maximization of displacements (in order to ensure the stability of the structural shape under operational loads, for example). Due to the presence of the inverse piezoelectric effect in the piezoelectric materials this problem can be solved by applying a predetermined voltage to the electrodes of the piezoelectric element. It is necessary to evaluate the ability of a piezoelectric element to influence the deformations of the object caused by external impact when using them in order to implement various structural mechanical behavior control strategies. This ability depends not only on the properties of a piezoelectric element (dimensions, material properties, location on the structure, etc.) and its structural characteristics (geometry, boundary conditions, material properties, etc.) but also on the operational loads of different kinds which impact a structure. One of the most convenient ways for estimating the influence of different factors on deformation of the structure under the electric voltage applied to piezoelectric elements is to use numerical modeling based on the finite element method. This modeling is performed on the basis of the well-known mathematical formulation of the static problem of electroelasticity. The possibilities of application of piezoelectric elements for changing the shape of an original object are shown by studying the examples where their number and location on a structure are varied. A cantilevered plate was considered as an object of study.